2010
DOI: 10.1007/s11424-010-8436-7
|View full text |Cite
|
Sign up to set email alerts
|

Global stability of an epidemic model for vector-borne disease

Abstract: This paper considers an epidemic model of a vector-borne disease which has the vectormediated transmission only. The incidence term is of the bilinear mass-action form. It is shown that the global dynamics is completely determined by the basic reproduction number R0. If R0 ≤ 1, the diseasefree equilibrium is globally stable and the disease dies out. If R0 > 1, a unique endemic equilibrium is globally stable in the interior of the feasible region and the disease persists at the endemic equilibrium. Numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…This model seems to be first suggested in [6,15] and it is now known as the Bailey-Dietz model. The global dynamics of this model was first studied in [18] using a Lyapunov function argument for the stability of the DFE, while the Poincaré-Bendixson property for 3-D competitive systems is used to show the stability of the EE; see also [8,89] for later similar studies. A global stability analysis using only Lyapunov functions has been obtained only recently- [74].…”
Section: Disease Dynamicsmentioning
confidence: 99%
“…This model seems to be first suggested in [6,15] and it is now known as the Bailey-Dietz model. The global dynamics of this model was first studied in [18] using a Lyapunov function argument for the stability of the DFE, while the Poincaré-Bendixson property for 3-D competitive systems is used to show the stability of the EE; see also [8,89] for later similar studies. A global stability analysis using only Lyapunov functions has been obtained only recently- [74].…”
Section: Disease Dynamicsmentioning
confidence: 99%
“…Wei discussed the global stability of an epidemic model for vector-borne disease and they showed that the global dynamics are completely determined by the basic reproductive number R 0 [39]. Belayneh, et al provided a cost effective control effort for treatment of hosts and prevention of vector-host contacts for a non-autonomous model, while they establish global stability conditions for the autonomous case [6].…”
Section: Yanzhao Cao and Dawit Denumentioning
confidence: 99%
“…Remark 3.3 It is worth mentioning that Yang et al (2010) studied a similar vector-host epidemic model with an SIR structure for the host population and without disease-induced host deaths. They used the method of the second additive compound matrix (see Li and Muldowney 1996 and references therein) to establish the global stability of the endemic equilibrium when it exists.…”
Section: Mathematical Analysismentioning
confidence: 99%